KOMPENSASI DAN KAITANNYA DENGAN KINERJA - Soliha, Euis (Fokus Ekonomi, 2006)
A tremendous amount of research has explored the relationship between managerial pay and firm performance. There are other criteria that can be used to determine managerial pay, as well as the influence of a firm’s governance structure and various contingencies. In recent years, many compensation researchers and consultans have been   advocating that the design of an effective reward system demands not only a close  articulation between human resource strategies and pay strategies, but also a clear fit between the compensation system and overall business strategies.  Keywords: Compensation, Firm Performance.